A Review on Recent Trends in Nanomaterials and Nanocomposites for Environmental Applications - Gopinath, Kannappan P.; Rajagopal, Malolan; Krishnan, Abhishek; Sreerama, Shweta Kolathur (Current Analytical Chemistry, 2021)
Background: Depletion and contamination of environmental resources such as water, air and soil caused by human activities is an increasingly important challenge faced around the world. The consequences of environmental pollution are felt acutely by all living beings, both on a short and long-term basis, thereby making methods of remediation of environmental pollution an urgent requirement. Objectives: The objective of this review is to dissect the complications caused by environmental degradation, highlight advancements in the field of nanotechnology and to scrutinize its applications in environmental remediation. Furthermore, the review aims to concisely explain the merits and drawbacks of nanotechnology compared to existing methods. Conclusion: The current and potential applications of nanomaterials and nanocomposites in the prevention, control and reduction of air, water and soil pollution and the mechanisms involved have been elucidated, with their various merits and demerits. The applications of nanotechnology in the fields of carbon capture and agriculture have also been discussed in this review.
Keywords: nanoparticles